1987
DOI: 10.1128/iai.55.10.2490-2495.1987
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a T-cell line specific for Rickettsia tsutsugamushi

Abstract: To study the immunological protective system against rickettsial infection, a T-cell line specific for Rickettsia tsutsugamushi antigen was established by long-term culture of splenocytes from mice immunized with live Gilliam strain R. tsutsugamushi and then propagated in the presence of homologous rickettsial antigen and syngeneic filler cells. The characteristics of the T-cell line and its capacity to induce antirickettsial protection in vivo were studied. Flow cytometric analysis demonstrated that the T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…IFN-␥ is important for protection in mice infected with Rickettsia spp. (20,28,30) and activates macrophages to secrete oxygen and nitrogen intermediates, such as NO, that are inhibitory for many intracellular pathogens, including rickettsiae (31,49). Soluble factors released by PBMC obtained from cattle during acute A. marginale infection and cultured with specific antigen were toxic for intraerythrocytic A. marginale (58).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-␥ is important for protection in mice infected with Rickettsia spp. (20,28,30) and activates macrophages to secrete oxygen and nitrogen intermediates, such as NO, that are inhibitory for many intracellular pathogens, including rickettsiae (31,49). Soluble factors released by PBMC obtained from cattle during acute A. marginale infection and cultured with specific antigen were toxic for intraerythrocytic A. marginale (58).…”
Section: Discussionmentioning
confidence: 99%
“…Interferon-␥ and IL-2 are both the products of CD4 + T (Th1) cells, and IFN-␥ has been shown to inhibit rickettsial growth in vitro and is believed to play an important role in resistance to rickettsial infection in vivo. 10,35,37,38 Moreover, Th1 cells are capable of inducing DTH and activating macrophages, making these cells particularly suited to deal with intracellular organisms.…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2 indicate that rickettsial antigen-specific T cell line can produce a factor which acts on macrophages infected with R. tsutsugamushi cytotoxically and selectively, and suggest the presence of another rickettsicidal mechanism in macrophages infected with rickettsiae. Moreover, we have reported that a rickettsial antigen-specific T cell line is able to produce gamma-interferon antigen-specifically (5), and it has also been reported that gammainterferon inhibits rickettsial growth in nonphagocytic cells (8). It seems to be more efficient for these soluble factors, cytotoxic lymphocytes and activated macrophages to inhibit the growth of rickettsiae in the host cooperatively.…”
mentioning
confidence: 87%